Yoga Intervention for Polycystic Ovary Syndrome: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Giridharan, Selvaraj; Ansar, Jawaher; Godbole, Mrunmai (International Research Journal of Ayurveda & Yoga, 2025)
Background: Polycystic ovary syndrome (PCOS) is a common endocrine disorder affecting women of reproductive age, characterized by insulin resistance, hyperandrogenism, and menstrual irregularities, which contribute to both metabolic and psychological challenges. Yoga therapy, as a holistic mind–body intervention, may provide benefits, although the evidence requires updating. This study aimed to assess the impact of yoga therapy on metabolic, endocrine, reproductive, and psychological outcomes in women with PCOS through a systematic review and meta analysis of randomized controlled trials (RCTs). Methods: Following the PRISMA 2020 guidelines, we searched PubMed, Embase, Cochrane, Scopus, and Google Scholar from January 2020 to May 2025 for RCTs on yoga for PCOS. Two reviewers screened the data, extracted the data, and assessed the risk of bias (RoB). Random-effects meta-analysis pooled outcomes and grading of recommendations assessment, development, and evaluation was used to evaluate certainty. Results: Eight RCTs involving 632 participants were included (median n = 52; moderate RoB). Yoga reduced metabolic homeostatic model assessment of insulin resistance (mean difference [MD] −0.58, 95% confidence interval [CI] −1.05–−0.11; I2 = 0%; moderate certainty), fasting insulin (MD −15.2 pmol/L, 95% CI −25.4–−5.0; I2 = 15%), testosterone (MD −10.44 ng/dL, 95% CI −14.12–−6.76; I2=19%), and depression (MD −4.69, 95% CI −5.63–−3.76; I2 = 75%; low certainty). Menstrual regularity improved (RR 1.45, 95% CI 1.10–1.92; I2 = 20%; moderate certainty). The effects on BMI and glucose levels were modest and uncertain. The subgroups showed greater benefits at ≥12 weeks/≥150 min/week. No adverse events. Conclusion: Yoga has demonstrated modest improvements in outcomes for individuals with PCOS, with moderate certainty regarding its metabolic and endocrine benefits. As a safe adjunctive therapy, it merits consideration for integration into patient care in the future. To confirm these findings over the long term, large multicenter RCTs with standardized protocols are required.